Efficacy of diclofenac sodium suppository as analgesic during Transrectal Ultrasound Guided Prostate biopsy - a single centre experience - Adzwani Mashudan (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Transrectal Ultrasound (TRUS) Guided Prostate biopsy is the most common day procedure in men in urology setup. As it involved multiple puncture using thick needle to gain the prostate tissue, it brings discomfort and pain to the involved patient. Thus periprostatic neural block is introduced to anaesthesize this prostate gland. Nevertheless, patient involved in this procedure still complaint pain during the biopsy. This pain they relate to the needle puncture during delivering the lidocaine to anaesthesize the prostate. Objective: In this study, our primary objective is to seek for the less invasive anesthesia method during TRUS biopsy of prostate that could provide similar anesthesia effect as periprostatic neural block. With this aim in mind we want to prove that intrarectal diclofenac suppository, a non-invasive method of analgesia, can give similar analgesic effect as periprostatic neural block during this procedure. Another primary focus of this research was to address the advantage of this less invasive methods of analgesia in detection of prostate carcinoma compare to periprostatic neural block. Methodology: A total of 100 patients recruited for this study where they are randomized into two arm. One arm using current periprostatic neural block (PNB) and another arm using suppository diclofenac sodium as analgesic. A questionnaire combining Visual Analogue Score (VAS) and Wong Baker FACEs pain scale developed to collect the data which is the pain score during the procedure. Result: this study showed median pain score of 2 (p=0.499) in both arm. The study also found no difference in pain score in both arm either being done by consultant urologist or by urology trainee.No significant association in detection of prostate cancer in between the two arm (p=0.25). Conclusion: Intrarectal diclofenac suppository is simple, less invasive and safe prostatic anaesthesia agent for TRUS guided prostate biopsy that give good analgesic property as periprostatic neural block. However, this less invasive method doesn't show any superiority in detection rate of prostate cancer compare to periprostatic neuralblock group.